Effects of salicylic acid on growth and accumulation of phenolics in Zea mays L. under drought stress - Latif, Farzana; Ullah, Faizan; Mehmood, Sultan; Khattak, Adnan; Khan, Asif Ullah; Khan, Safiullah; Husain, Ishtiaq (Acta agriculturae Scandinavica. Section B, Soil and plant science, 2016)
The accumulation of total soluble and cell wall-bound phenolics and total soluble proteins in Zea mays plants exposed to drought stress and foliar spray of salicylic acid (SA) at 10 ⁻⁴ mol/L and 10 ⁻⁵ mol/L was investigated. Drought stress was imposed at the four-leaf stage for 10 days (30–35% field capacity). Dehydration of maize leaves was accompanied by the accumulation of both total soluble and cell wall-bound phenolics, reduction in leaf relative water content (LRWC), and shoot and root growth attributes. Foliar spraying of SA further augmented the content of total soluble and cell wall-bound phenolics and total soluble proteins content under drought stress. SA ameliorated the adverse effects of drought stress on LRWC, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, root length and root area. The accumulation of both soluble and cell wall-bound phenolics by foliar spray of SA may be a mechanism related to SA-induced drought stress tolerance in maize. It was concluded that foliar spraying of SA at 10 ⁻⁵ mol/L can be highly economical and effective for modifying the effects of drought stress on maize at the four-leaf stage.